2023
DOI: 10.1007/s00421-023-05287-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 7-day polyphenol powder supplementation on cycling performance and lung function in an ozone-polluted environment

Abstract: Purpose Polluted environments can adversely affect lung function and exercise performance. Evidence suggests that some nutrient supplements may offset pollution’s detrimental effects. This study examined the effect of polyphenol supplementation on lung function and exercise performance in an ozone-polluted environment. Methods Ten male cyclists (mean ± SD: age, 43.8 ± 12.4 years; height, 177.8 ± 7.1 cm; weight, 76.03 ± 7.88 kg; VO2max 4.12 ± 0.72 L min−1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Conversely, studies on Montmorency cherry supplementation have shown higher baseline muscle oxygenation, but no effect during a moderate- or severe-intensity exercise bout [ 24 , 25 ]. Similarly, polyphenol supplementation for 7 d was not sufficient to affect any muscle oxygenation metric during a 4-km cycling TT [ 26 ]. When looking at the maximal muscle deoxygenation during exercise, a study on the polyphenols mangiferin and luteolin found that they significantly lowered muscle O 2 levels during a 30-s Wingate test after consumption for 48 h and 15 d, which they attributed to an improved ability of the muscle to extract oxygen [ 27 ], conversely to what we observed.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, studies on Montmorency cherry supplementation have shown higher baseline muscle oxygenation, but no effect during a moderate- or severe-intensity exercise bout [ 24 , 25 ]. Similarly, polyphenol supplementation for 7 d was not sufficient to affect any muscle oxygenation metric during a 4-km cycling TT [ 26 ]. When looking at the maximal muscle deoxygenation during exercise, a study on the polyphenols mangiferin and luteolin found that they significantly lowered muscle O 2 levels during a 30-s Wingate test after consumption for 48 h and 15 d, which they attributed to an improved ability of the muscle to extract oxygen [ 27 ], conversely to what we observed.…”
Section: Discussionmentioning
confidence: 99%
“…Full details of the exercise testing regimes and exercise endpoints have been reported elsewhere [ 43 ]. In brief, subjects were randomly assigned in a double-blind crossover design to receive either PL or POLY for 7 days prior to exercise and cognitive testing.…”
Section: Methodsmentioning
confidence: 99%
“…The POLY supplement was a commercially available combination of freeze-dried NZ blackcurrant (94%; Delphinidin-3-0-Glucoside, 176 mg/5 g, Delphinidin-3-0-Rutinoside, 752 mg/5 g, Cyanidin-3-0-Glucoside, 84 mg/5 g, Cyanidin-3-0-Rutinoside, 722 mg/5 g, Total Anthocyanins, 1733.5 mg/5 g), L-theanine (3%), and Pinus radiata extract (3%) (Ᾱrepa™), and was prescribed as a relative dose of 4.3 mg anthocyanins/kg −1 . A berry-flavored powder that contained no vitamin C, active ingredients, or phenolics was used as the PL [ 43 ]. The POLY and PL were equivalent in energy and carbohydrate content (per 5 g—POLY: 15 cal, carbohydrate 3 g, PL: 16 cal, carbohydrate 3.6 g).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation